EZH2 inhibitor tazemetostat in patients with relapsed or refractory, BAP1-inactivated malignant pleural mesothelioma: a multicentre, open-label, phase 2 study. Issue 6 (June 2022) - Zauderer, Marjorie G; Szlosarek, Peter W; Le Moulec, Sylvestre; Popat, Sanjay; Taylor, Paul; Planchard, David; Scherpereel, Arnaud; Koczywas, Marianna; Forster, Martin; Cameron, Robert B; Peikert, Tobias; Argon, Evren Kocabaş; et al.
Summary: Background: Treatment options for malignant pleural mesothelioma are scarce. Tazemetostat, a selective oral enhancer of zeste homolog 2 (EZH2) inhibitor, has shown antitumour activity in several haematological cancers and solid tumours. We aimed to evaluate the anti-tumour activity and safety of tazemetostat in patients with measurable relapsed or refractory malignant pleural mesothelioma. Methods: We conducted an open-label, single-arm phase 2 study at 16 hospitals in France, the UK, and the USA. Eligible patients were aged 18 years or older with malignant pleural mesothelioma of any histology that was relapsed or refractory after treatment with at least one pemetrexed-containing regimen, an Eastern Cooperative Oncology Group performance status of 0 or 1, and a life expectancy of greater than 3 months. In part 1 of the study, participants received oral tazemetostat 800 mg once on day 1 and then twice daily from day 2 onwards. In part 2, participants received oral tazemetostat 800 mg twice daily starting on day 1 of cycle 1, using a two-stage Green-Dahlberg design. Tazemetostat was administered in 21-day cycles for approximately 17 cycles. The primary endpoint of part 1 was the pharmacokinetics of tazemetostat and its metabolite at day 15 after administration of 800 mg tazemetostat, as measured by maximum serum concentration (Cmax ), time to Cmax (Tmax ), area under the concentration-time curve (AUC) to day 15 (AUC0–t ), area under the curve from time 0 extrapolated to infinity (AUC0–∞ ), and the half-life (t1/2 ) of tazemetostat, assessed in all patients enrolled in part 1. The primary endpoint of part 2 was the disease control rate (the proportion of patients with a complete response, partial response, or stable disease) at week 12 in patients with malignant pleural mesothelioma per protocol with BAP1 inactivation determined by immunohistochemistry. The safety population included all the patients who had at least one post-dose safety assessment. This trial is now complete and is registered with ClinicalTrials.gov, NCT02860286 . Findings: Between July 29, 2016, and June 2, 2017, 74 patients were enrolled (13 in part 1 and 61 in part 2) and received tazemetostat, 73 (99%) of whom had BAP1 -inactivated tumours. In part 1, following repeat dosing of tazemetostat at steady state, on day 15 of cycle 1, the mean Cmax was 829 ng/mL (coefficient of variation 56·3%), median Tmax was 2 h (range 1–4), mean AUC0–t was 3310 h·ng/mL (coefficient of variation 50·4%), mean AUC0–∞ was 3180 h·ng/mL (46·6%), and the geometric mean t1/2 was 3·1 h (13·9%). After a median follow-up of 35·9 weeks (IQR 20·6–85·9), the disease control rate in part 2 in patients with BAP1 -inactivated malignant pleural mesothelioma was 54% (95% CI 42–67; 33 of 61 patients) at week 12. No patients had a confirmed complete response. Two patients had a confirmed partial response: one had an ongoing partial response with a duration of 18 weeks and the other had a duration of 42 weeks. The most common grade 3–4 treatment-emergent adverse events were hyperglycaemia (five [7%] patients), hyponatraemia (five [7%]), and anaemia (four [5%]); serious adverse events were reported in 25 (34%) of 74 patients. Five (7%) of 74 patients died while on study; no treatment-related deaths occurred. Interpretation: Further refinement of biomarkers for tazemetostat activity in malignant pleural mesothelioma beyond BAP1 inactivation could help identify a subset of tumours that are most likely to derive prolonged benefit or shrinkage from this therapy. Funding: Epizyme.